Ground transport stress affects bacteria in the rumen of beef cattle: A real‐time PCR analysis. (3rd October 2016) - Deng, Lixin; He, Cong; Zhou, Yanwei; Xu, Lifan; Xiong, Huijun
Abstract: Transport stress syndrome often appears in beef cattle during ground transportation, leading to changes in their capacity to digest food due to changes in rumen microbiota. The present study aimed to analyze bacteria before and after cattle transport. Eight Xianan beef cattle were transported over 1000 km. Rumen fluid and blood were sampled before and after transport. Real‐time PCR was used to quantify rumen bacteria. Cortisol and adrenocorticotrophic hormone (ACTH) were measured. Cortisol and ACTH were increased on day 1 after transportation and decreased by day 3. Cellulolytic bacteria ( Fibrobacter succinogenes and Ruminococcus flavefaciens ), Ruminococcus amylophilus and Prevotella albensis were increased at 6 h and declined by 15 days after transport. There was a significant reduction in Succinivibrio dextrinosolvens, Prevotella bryantii, Prevotella ruminicola and Anaerovibrio lipolytica after transport. Rumen concentration of acetic acid increased after transport, while rumen pH and concentrations of propionic and butyric acids were decreased. Body weight decreased by 3 days and increased by 15 days after transportation. Using real‐time PCR analysis, we detected changes in bacteria in the rumen of beef cattle after transport, which might affect the growth of cattle after transport.